Expression of phytase From Mitsuokella jalaludinii in heterologous hosts and characterization of expressed protein from escherichia coli - Tan, Wan Qin (2013)
Phytase is an enzyme which catalyzes the hydrolysis of phytate to release lower inositol phosphate and usable form of inorganic phosphate. It plays an important role in the breakdown of phytate present in the plant-based animal feed, especially poultry, fish, and swine which lack of natural phytase in their digestive systems to improve the bioavailability of phytate-phosphorus, nutritionally important minerals,and growth performance. In our laboratory, a strict anaerobic phytase-producing rumen bacterium, Mitsuokella jalaludinii was isolated and a comparative study on the freeze-dried active M. jalaludinii culture (FD-AMJC) and commercial Natuphos® phytase (phytase-N) revealed that the overall effect of feed conversion rate, phosphorus and calcium retention, dry matter digestibility and phosphorus excretion in the FD-AMJC was better than phytase-N. However, due to the strict anaerobic growth mode of M. jalaludinii, the mass production of the viable culture as feed supplement is restricted. In the present study, the 1.05 kb phytase gene which was previously cloned in pCR2.1TOPO plasmid was amplified by Polymearse Chain Reaction (PCR) and subcloned into Pichia pastoris expression vectors (pGAPZαC and pPIC6αA) and Escherichia coli expression vector (pET32a). The amplified gene sequence showed 99% similarity with native phytase gene. The pGAPphy and pPICphy were transformed into Pichia pastoris X-33 for extracellular expression,while the pPETphy was transformed into E. coli Rosetta-gami for intracellular expression of recombinant phytase. Expression was only observed in E. coli Rosettagami transformants but not P. pastoris transformants. Thus, only the recombinant phytase from E. coli Rosetta-gami was used for subsequent characterization. Based on the SDS-PAGE analysis, the size of the purified recombinant phytase expressed by E. coli Rosetta-gami was estimated to be 55 kDa by SDS-PAGE analysis. The purification by His-Trap one step purification column produced 1.8-fold higher yield than the unpurified fraction with the enzyme activity of 303 U/mg. The recombinant phytase exhibited its highest enzyme activity at 55 °C and pH 4.5. The enzyme was stable at a broad pH range from 3.5 to 5.5 with more than 78% relative activity retained after 1 h exposure. The recombinant phytase was slightly inhibited by copper (5.9%) and EDTA (15.8%) and was greatly inhibited by ferum (76.6%) and zinc (78.5%) at 1.0 mM concentration. Nevertheless, calcium, potassium, and magnesium were found to enhance phytase activity with increment of activity to 148.8%, 118.3%, and 103.4%, respectively, at 1.0 mM concentration. Besides, the enzyme activity was found to be reduced when 0.05 to 10.0 mM phosphate was present in the reaction mixture. The digestive enzyme sensitivity analyses had revealed that the recombinant phytase was susceptible to pepsin proteolysis with only retention of 23.7% relative activity, but less affected to trypsin degradation with retention of 78.8% relative activity after pre-treatment of recombinant phytase with respective digestive enzymes at 37 °C for 1 h. The present findings showed that phytase from Mitsuokella jalaludinii can be expressed from Escherichia coli Rosettagami under IPTG induction and possesses moderate temperature profile, good pH tolerance, and pepsin stability, which indicates that with further study, the recombinant phytase can be a potential candidate as feed enzyme.